PID-Controlled Gyroscopic Stabilization for Roll Balancing: A Simulation and Experimental Study - Crisnapati, Padma Nyoman; Putu Devi Novayanti; Ni Ketut Ira Permata Adi; I Putu Agung Mas Aditya Warman; Anak Agung Istri Cintya Prabandari; I Made Darma Susila (Jurnal Sistem Komputer dan Informatika (JSON), 2025)
In marine engineering, stabilizing boat roll motion under wave-induced disturbances is a crucial problem where traditional approaches frequently have drawbacks in terms of responsiveness, energy efficiency, and adaptability. In this study, a PID-controlled gyroscopic stabilization system for boat roll balancing is designed, simulated, and experimentally validated. To capture the coupled dynamics of servo motor behavior, gyroscopic torque generation, and boat roll motion, a thorough dynamic model was created. Four gain configurations—Low, Moderate, High, and Very High—were evaluated using the model-guided PID parameter tuning that was implemented in Python. The mechanical system incorporates a gyroscopic flywheel driven by BLDC and mounted on a servo-controlled cradle. An ESP32 microcontroller processes real-time roll angle feedback from an MPU6050 sensor. According to simulation results, the ideal balance between rise time (~300 ms), overshoot (~2°), and settling time (~1 s) was reached with moderate PID gains. While High and Very High gains displayed instability because of unmodeled vibrations and sensor noise, a scaled physical prototype that was built and tested under controlled disturbances demonstrated strong alignment with simulation trends for Low and Moderate gains. The results show that moderate gains, which offer both quick stabilization and reliable performance, offer the most useful configuration for real-world applications. This work contributes a validated methodology for optimizing PID-controlled systems in dynamic environments by bridging the gap between theoretical modeling and practical implementation of marine gyroscopic stabilization.